Pelatihan Pemanfaatan Potensi Kayu Lokal Untuk Mendukung Sektor Pariwisata pada Kelompok Pemuda Desa Aur Sati Kecamatan Tambang Kampar Riau - Nurdin, Nurdin; Fakhri, Fakhri; Ermiyati, Ermiyati; Morena, Yenita; Suprayogi, Imam; Fauzi, Manyuk; Novan, Andre (Pelita Masyarakat, 2024)
The potential of local wood and the large amount of wood waste from the wood processing industry and window and frame businesses in Aur Sati Village, Tambang District, Kampar Regency, need to be utilized by the community so that training is needed to utilize local wood potential to support the tourism sector for youth groups and PKK mothers in the village. The purpose of this activity is to assist in optimizing processed wood waste to add economic value, and it is hoped that the results of this activity can provide knowledge and technology for utilizing local wood resources so that in the future it will be able to increase community income to support the tourism sector. The activity results have been applied as decorative table products from Durian tree trunks that are no longer productive and processed wood waste from the community. The products produced in terms of visual appearance have distinctive characteristics and look classic, so they will have a fairly high selling price. The results of this community service activity are in the form of assistance to the target audience in the form of training/counseling on making decorative tables from pieces of Durian tree trunks that are no longer productive and processed waste from the community.